Improving a process in a brazilian automotive plant applying process mapping, Design of Experiments and Discrete Events Simulation - Montevechi, José Arnaldo Barra; De Pinho, Alexandre Ferreira; Leal, Fabiano; Marins, Fernando Augusto Silva [UNESP]; Costa, Rafael Florêncio Da Silva (My University, 2008)
The objective of this article is to apply the Design of Experiments technique along with the Discrete Events Simulation technique in an automotive process. The benefits of the design of experiments in simulation include the possibility to improve the performance in the simulation process, avoiding trial and error to seek solutions. The methodology of the conjoint use of Design of Experiments and Computer Simulation is presented to assess the effects of the variables and its interactions involved in the process. In this paper, the efficacy of the use of process mapping and design of experiments on the phases of conception and analysis are confirmed.
Keywords: Design of Experiments; Discrete Events Simulation; Process Mapping; Automotive plants; Automotive process; Discrete events simulation; Process mapping; Simulation process; Trial and error; Computer simulation; Mapping; Design of experiments